PENGELOLAAN KEUANGAN BAGI MAHASISWI ASRAMA YANG TINGGAL DI SEKITAR KAMPUS UNIVERSITAS RIAU PANAM PEKANBARU - Liana, Sri; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is done at campuses surrounding garrison Riau Panam Pekanbaru's University correct it at Jasmine garrison. This research intent know financial management trick Jasmine garrison coed and coed way bridges over finance. This research is entitled “Financial management For Remained Garrison Coed Campus Around Riau Panam Pekanbaru's University ”.   Observational subject problem it is how coed utilize remittance money that given by oldster and bridging over financially at month end when remittance was coming. Sample take in observational it is with purposive's tech. total sample which is 10 person. Method that is utilized is kualitatif's method Descriptive with kualitatif's data analysis. Data winnow instrument that is utilized is observation, interview and documentation. Observational result therefore researcher points out: Coed that lives in Jasmine garrison in brings off financially each month it a considerable part difficult to control because doesn't make financial expenditure plan this ordinarily evident prodigal life already innate since before college and also since friend influence. Make the point coed that lives in Jasmine garrison bridge over finance or last strategy lives at while month end first utilize active strategy which is strategy which mengotimalkan all family potency which is by calls up oldster when depleted money, Both of passive Strategy which is with reduce family expenditure which is by eats patch up, Strategy third network which is interlace relationship which is by borrows money to friend and eating with comate when month end. Key word: Management, Financially, Coed